Surface‐Shielding Nanostructures Derived from Self‐Assembled Block Copolymers Enable Reliable Plasma Doping for Few‐Layer Transition Metal Dichalcogenides. (7th June 2016) - Yim, Soonmin; Sim, Dong Min; Park, Woon Ik; Choi, Min‐Jae; Choi, Jaesuk; Jeon, Jaebeom; Kim, Kwang Ho; Jung, Yeon Sik
Abstract : Precise modulation of electrical and optical properties of 2D transition metal dichalcogenides (TMDs) is required for their application to high‐performance devices. Although conventional plasma‐based doping methods have provided excellent controllability and reproducibility for bulk or relatively thick TMDs, the application of plasma doping for ultrathin few‐layer TMDs has been hindered by serious degradation of their properties. Herein, a reliable and universal doping route is reported for few‐layer TMDs by employing surface‐shielding nanostructures during a plasma‐doping process. It is shown that the surface‐protection oxidized polydimethylsiloxane nanostructures obtained from the sub‐20 nm self‐assembly of Si‐containing block copolymers can preserve the integrity of 2D TMDs and maintain high mobility while affording extensive control over the doping level. For example, the self‐assembled nanostructures form periodically arranged plasma‐blocking and plasma‐accepting nanoscale regions for realizing modulated plasma doping on few‐layer MoS2, controlling the n‐doping level of few‐layer MoS2 from 1.9 × 10 11 cm −2 to 8.1 × 10 11 cm −2 via the local generation of extra sulfur vacancies without compromising the carrier mobility. Abstract : Rigid surface‐shielding nanostructures are fabricated on few‐layer transition metal dichalcogenides transistors by self‐assembly of silicon‐containing block copolymers. With precisely controlled plasma‐accepting and plasma‐protecting regions, desulfurization at the plasma‐accepting regions leads to n‐doping effect without compromising the pristine carrier mobility. In addition, doping concentration and types are controlled by adjusting process parameters.